Deposition of thin metal films by intense ion beams on metals; Technical Physics Letters; Vol. 22, iss. 4 - Remnev (Remnyov) G. E. Gennady Efimovich; Zakutaev A. N.; Ivanov Yu. F. Yuriy Fedorovich; Matvienko M. V.; Potemkin A.V. (1996, 1996)
Title screen